2014
DOI: 10.4097/kjae.2014.67.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative predictors of early tracheal extubation after living-donor liver transplantation

Abstract: BackgroundProlonged mechanical ventilation after liver transplantation has been associated with deleterious clinical outcomes, so early tracheal extubation posttransplant is now increasing. However, there is no universal clinical criterion for predicting early extubation in living-donor liver transplantation (LDLT). We investigated specific predictors of early extubation after LDLT.MethodsPerioperative data of adult patients undergoing LDLT were reviewed. "Early" extubation was defined as tracheal extubation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 26 publications
2
20
1
Order By: Relevance
“…The incidence of immediate extubation (32.1%) was noticeably lower than those reported by other studies (58% to 83.5%) 1,2,4,5 . However, a subgroup analysis indicated that the incidence rose by 56.4% from 2011 to 2016, which is comparable with the findings of other studies.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The incidence of immediate extubation (32.1%) was noticeably lower than those reported by other studies (58% to 83.5%) 1,2,4,5 . However, a subgroup analysis indicated that the incidence rose by 56.4% from 2011 to 2016, which is comparable with the findings of other studies.…”
Section: Discussionsupporting
confidence: 74%
“…Orthotopic liver transplantation (OLT) has been used to treat acute and chronic end‐stage liver disease for nearly five decades 1 . In the past, post‐liver transplant patients required mechanical ventilation with sedation or analgesia for more than 24 h due to prolonged surgery, massive blood transfusion, and high‐volume fluid administration 2 . Current evidence, however, suggests that positive pressure ventilation may have deleterious effects on graft outcomes due to liver congestion from high venous pressure, 1,3,4 suggesting that patients may benefit from earlier withdrawal from mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…F–M in Appendix 2). In addition, regarding Child C status (%), one study [ 27 ] adopted the data form of Child B+C %, however, it did not change the pooled effect as removed from the main analysis (Fig. N in Appendix 2).…”
Section: Resultsmentioning
confidence: 99%
“…All the studies used patients’ medical records for their analyses (Table 2 ). The IPTE exposures were inconsistent across those studies, 7 [ 9 , 20 23 , 25 , 27 ] studies described the detailed time interval, but 3 [ 24 , 26 , 28 ] studies failed to give the detailed description. We sparingly pigeonholed the 3 ones as “< 8 hours ν control,” with the risk of adjustment questionable.…”
Section: Resultsmentioning
confidence: 99%